EXTH-36. MRGFUS-DELIVERED FLUORESCENT EGFR/EGFRVIII ANTIBODY ENABLES THERANOSTIC IMAGING OF PEDIATRIC HIGH-GRADE GLIOMA AND PREDICTS RESPONSE TO TARGETED THERAPY. (14th November 2022) - Zhou, Quan; Aryal, Muna; Leonel, Johana Vega; Santoso, Michelle; Zlitni, Aimen; Vogel, Hannes; Cayrol, Romain; Li, Gordon; Moseley, Michael
Abstract: BACKGROUND: Pediatric high-grade glioma (pHGG) consists of the deadliest childhood brain cancers refractory to current therapies. Fluorescent antibodies against epidermal growth factor receptor (EGFR) have demonstrated clinical promise in image-guided surgery of adult gliomas. However, their potential theranostic use for pHGG remains unexamined. This study evaluated an EGFR/EGFRvIII-targeted imaging and treatment strategy as an alternative therapeutic approach for pHGG using tracer amount of fluorescent antibody delivered through blood-brain barrier modulation. METHODS: Immunohistochemical stainings of EGFR, EGFRvIII and claudin-5 were performed on pHGG patient tissue (n = 66). In vitro competition assay assessed binding affinity of panitumumab-IRDye800 for EGFR/EGFRvIII on pHGG cells whose viability was measured upon panitumumab treatment. Mice with EGFR/EGFRvIII-positive orthotopic pHGG patient-derived xenografts received 1 mg/kg panitumumab-IRDye800 20 hours after transcranial magnetic resonance-guided focused ultrasound (MRgFUS) sonication (2 min at 0.25 MPa). Near-infrared fluorescence imaging measured tumor-to-background ratio and TUNEL assay determined apoptotic rate in resected tumor. Survival was documented for 60 days in pHGG-bearing mice receiving 1 mg/kg panitumumab weekly with or without MRgFUS. RESULTS: 61% and 24% pHGG patient tissue respectively expressed EGFR and EGFRvIII (17% expressing both). Heterogeneous claudin-5 expression indicated partial blood-brain barrier permeability. Panitumumab-IRDye800 bound to EGFR/EGFRvIII-positive pHGG with high affinity (IC50: 4.2 nM). EGFR blocking enhanced therapeutic response of panitumumab by 48 ± 13%. Following MRgFUS in pHGG-bearing mice, 19 ± 6.3% injected dose of intratumoral panitumumab-IRDye800 uptake resulted in 2.1 ± 0.4 tumor contrast and 3.9 ± 1.1% apoptotic cell death. Weekly MRgFUS with 1 mg/kg panitumumab prolonged median survival (27.5 vs. 17.5 days, P < 0.0001, n = 10). CONCLUSION: Tracer dose of panitumumab-IRDye800 improved tumor contrast and predicted antitumor activity via EGFR/EGFRvIII dual targeting following MRgFUS, potentially benefiting 68% of pHGG population. Reduced therapeutic dose of panitumumab by EGFRvIII-focused targeting may improve treatment safety and efficacy against EGFRvIII-stratified gliomas.